Pilot study of long-term anaesthesia in broiler chickens. (January 2016) - O'Kane, Peter M; Connerton, Ian F; White, Kate L
Abstract: Objective: To provide stable anaesthesia of long duration in broiler chickens in order to perform a terminal caecal ligated loop procedure. Study design: Prospective experimental study. Animals: Seven clinically healthy broiler chickens ( Gallus domesticus ) aged 27-36 days, weighing 884-2000 g. Methods: Anaesthesia was induced and maintained with isoflurane in oxygen. All birds underwent intermittent positive pressure ventilation for the duration. End-tidal carbon dioxide, peripheral haemoglobin oxygen saturation, heart rate and oesophageal temperature were monitored continuously. All birds received intraosseous fluids. Butorphanol (2 mg kg −1 ) was administered intramuscularly at two hourly intervals. Euthanasia by parenteral pentobarbitone was performed at the end of procedure. Results: Stable anaesthesia was maintained in four chickens for durations ranging from 435 to 510 minutes. One bird died and one was euthanized after 130 and 330 minutes, respectively, owing to surgical complications and another died from anaesthetic complication after 285 minutes. Conclusions and clinical relevance: Long-term, stable anaesthesia is possible in clinically healthy chickens, provided complications such as hypothermia and hypoventilation are addressed and vital signs are carefully monitored. There are no known previous reports describing monitored, controlled anaesthesia of this duration in chickens.